TRUTH OR TEMPERAMENT: A Fresh Approach to the Study of the Comparative Religion Arvind Sharma - Sharma , Arvind (Journal of Dharma, 2002)
It is now almost a century since the inception of the comparative study of religion. As the data on religion from all parts of the world continues to be collected and collated, the suggestion has been made that one might now speak of the religion of man/woman in the singular rather than of the religions of man/woman in the plural. In any case, the data on the religious life of man/woman is capable of being viewed as a single entity when it comes to academic study of religion.